Membangun Lingkungan Pendidikan Yang Kreatif, Kritis, Dan Berakhlak - Fandi Kurniawan; Abdul Khobir; Muhammad Tastafiyan el-mudaafi; Achmad Fauzi (Advances In Education Journal, 2025)
The educational environment plays a vital role in shaping students into creative, critical, and morally upright individuals. This article explores the meaning and significance of an ideal educational environment, including strategies to foster creativity through literacy activities, extracurricular programs, and brainstorming methods. It also discusses the importance of developing critical thinking skills in the digital era, where students must be able to evaluate information logically and responsibly. Furthermore, moral and character education is emphasized as a fundamental pillar in addressing the current moral crisis among students. This study employs a descriptive qualitative approach through library research by analyzing relevant literature on creative learning, critical thinking development, and moral education. The findings reveal that an innovative educational environment—supported by collaboration between schools, families, and communities—can produce a generation that is not only intellectually capable but also possesses strong character and noble morals, enabling them to face future challenges effectively.